Callus induction from the leaves of Ipomoea batatas (sweet potato) / Nor Atikah Ismail - Ismail, Nor Atikah (2019)
Sweet potato (Ipomoea batatas) is vital crops that are consumed in several countries such as China and Africa. However, only the tubers of sweet potato are use up by many people but the other parts such as leaves and stems are usually discarded. Based on previous study, the leaves of sweet potato plant actually contain secondary metabolite. It is proved through a research conducted by Muhamad Ridzuan (2017). The results from his study had revealed the presented of unknown alkaloid in leaves of sweet potato consumed from the wild type plant sample. As published, alkaloid may be used in treatment of disease such as an ovarian cancer. Therefore, the comparison of alkaloid that presented within the callus induced from this study and the wild type plant will be done. Thus, the purpose of this research is to induce the callus from leaves of sweet potato by using different types of hormones such as 2,4-dichlorophenoxyacetic acid (2,4-D), napthaleneacetic acid (NAA) and indole-3-acetic acid (IAA) at different concentrations. Besides from that, the aim of this study is to compare the callus induction from leaves of sweet potato with different types of phytohormone such as, 2,4-dichlorophenoxyacetic acid (2,4-D), napthaleneacetic acid (NAA) and indole-3-acetic acid (IAA) at different concentrations (1.0, 2.0, 3.0, 4.0 and 5.0 mg/L). The explants were cultured in media that contain phytohormone and were observed in 30 days. At the end of research, there can be seen that the best hormone induced callus was IAA, followed by 2,4-D. Unfortunately, there was no callus induced through NAA. Based on concentration, the highest percentage of callus was induced by IAA at 3.0 (13.33%). Meanwhile, the percentage of callus induced by 2,4-D was at 1.0 and 4.0 mg/L concentration (6.67%). For the narrowed down concentration of 2,4-D, the highest percentage of callus was induced at concentration 2.0 mg/L of 2,4-D (20.00%). From the physical appearance, after 4 days it can be seen that the entire callus induced are in white callus. Based on the result, the present of secondary metabolites such as alkaloid can be detected through Thin Layer Chromatography (TLC) from the callus induced. Therefore, the optimization of callus growth by using different media and formulation of concentration phytohormone can be done. In addition, the concentration of the alkaloid can be obtained through High Performance Liquid Chromatography (HPLC).